Food Insecurity: A Constant Factor in the Lives of Low-Income Families in Scotland and England - Shinwell, Jackie; Defeyter, Margaret Anne (Frontiers in Public Health, 2021)
During the school summer holidays, pressures on the already tight budgets of low-income families are compounded, particularly when the safety net of free school meals is removed. In this study, we used purposive sampling to recruit a total of 21 parents (N= 20 Female, N= 1 Male) whose children attended free summer holiday clubs during summer 2017 that had been set up to enable children from low-income families to access food and enriching activities. Data were collected in clubs located in Scotland and England as these countries had broadly similar free school meal policies and models of holiday club delivery in place at the time of data collection. Participants were asked about their food and shopping habits during the school term and if, and how they differed during the school summer holidays when free school meals were not available. The findings suggest that food insecurity is a constant factor in the lives of low-income parents in England and Scotland, and that the stages of food insecurity and the coping strategies employed to mitigate its effects appear to be cyclical and align with Food and Agriculture Organisation’s (FAO) food insecurity continuum, and the school academic year. During term time, parents and carers worried about food, suggesting they were experiencing mild food insecurity. As the school holidays approached, parents began “provisioning”, storing food and trying to save money in anticipation of children being at home all day, bored and constantly hungry. However, food did not last, and parental food acquisition habits became more intense. Parents downgraded food brands, shopped on-line to reduce “pester power” and to monitor spending and remove items from shopping baskets. When they shopped, they hunted for bargains, bought reduced price items of food that were then stored in a freezer. Parents self-sacrificed their needs, only buying and cooking meals that children would eat, that were ‘bulked up’ with cheaper foods such as hot dogs and noodles. However, children’s attendance at holiday club helped make the food at home last longer and once school resumed, parents returned to their less intense, but constantly coping approach to food shopping.